2009
DOI: 10.4072/rbp.2009.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volcanic ash-fall on a Permian peat-forming environment, on the basis of palynology, palynofacies and paleobotany (Faxinal Coalfield, Brazil)

Abstract: -The aim of this paper was to assess, in a study case, whether ash-fall deposition influenced the character of the peat-forming vegetation in some coal beds in the southernmost Paraná Basin in Brazil, taking into consideration that records of tonstein levels are common in some coal bearing-strata. An investigation was made of the uppermost Faxinal coal seam (Coal Seam S), which displays two adjacent coal beds interbedded with a tonstein level. On the basis of the botanical affinity between the miospores and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…8F, H, J) observed in all palynomorphs (pollen grains, spores, and algal elements) indicates the reestablishment of moisture and peat-forming conditions, even though episodes of wildfires occurred. The severe decrease in the number of dispersed trilete spores in relation to the lower level suggests a change in the proportion of the main vegetation groups immediately following ash fall, and is in agreement with previous palynological and palynofaciological analyses of the coal seam S (Cazzulo-Klepzig et al, 2009;Simas et al, 2013). The increased dominance of bissacate pollen grains over pteridophytic spores after the ash fall indicates that the glossopterid vegetation was not suppressed by the fire, and a new niche was not opened for recolonization.…”
Section: Fluorescence Observation Of Dispersed Organic Mattersupporting
confidence: 78%
See 1 more Smart Citation
“…8F, H, J) observed in all palynomorphs (pollen grains, spores, and algal elements) indicates the reestablishment of moisture and peat-forming conditions, even though episodes of wildfires occurred. The severe decrease in the number of dispersed trilete spores in relation to the lower level suggests a change in the proportion of the main vegetation groups immediately following ash fall, and is in agreement with previous palynological and palynofaciological analyses of the coal seam S (Cazzulo-Klepzig et al, 2009;Simas et al, 2013). The increased dominance of bissacate pollen grains over pteridophytic spores after the ash fall indicates that the glossopterid vegetation was not suppressed by the fire, and a new niche was not opened for recolonization.…”
Section: Fluorescence Observation Of Dispersed Organic Mattersupporting
confidence: 78%
“…a decrease in lycopsids and filicopsids spores and an increase from 56% to 80% in the frequency of gymnosperm pollen grains from base to top (Cazzulo-Klepzig et al, 2009). However, Boardman et al (2012) reported a relative frequency of 24% of Zygnemaphyceae algae for the coal underlying the tonstein.…”
Section: Geological and Paleontological Contextmentioning
confidence: 95%
“…The dispersed fragments of Noeggerathiopsis brasiliensis are accessory fossils in the paleofloristic association of the Faxinal tonstein layer (southernmost Brazilian Gondwana), which was largely dominated by Glossopteris leaves as previously described by Guerra-Sommer (1992), Boardman et al (2012), Degani-Schmidt et al (2015) and Degani-Schmidt & Guerra-Sommer (2016b). However, the cordaitalean pollens are well represented in the underlying coalbeds, supporting their contribution to the original coal biomass (Cazzulo-Klepzig et al 2009). Additionally, unlike the glossopterids, which were restricted to the southern megacontinent of Gondwana, the cordaitalean paleobiogeography has worldwide significance.…”
Section: Floristic Association and Paleoenvironmental Significancesupporting
confidence: 67%
“…Palynological and palynofacies analyses of the tonstein layer (Cazzulo-Klepzig et al 2009, Degani-Schmidt et al 2015 revealed the dominance of phytoclasts and poorly preserved sporomorphs. Monosaccate and bisaccate pollen grains were dominant (e.g., Cannanoropollis Potonié and Sah and Scheuringipollenites Tiwari), occurring together with Protohaploxypinus (Samoilovich) Morbey.…”
Section: Floristic Association and Paleoenvironmental Significancementioning
confidence: 99%
“…Previously, the palynofacies analysis was only confined to the marine settings solely for the petroleum sectors. It has not only played a substantial role in the palaeoenvironmental settings in the marine succession (Götz et al 2003;Oboh-lkuenobe et al 2005;Hermann et al 2012;Carvalho et al 2013;El Atfy et al 2014) but also has been applied on the continental successions of different sedimentary horizons, including coal/lignite (Singh et al 1992;Closas et al 2005;Cazzulo-Klepzig et al 2009;Götz 2016, 2017;Cornamusini et al 2017;Götz et al 2017;Aggarwal et al 2019a, b, c). The palynofacies study has now been expanded in various types of lacustrine (Aggarwal et al 2019b) and fluvial systems delineating its importance to coal deposits (Aggarwal et al 2019a, b, c), understanding the processes and factors responsible for the sediment deposition.…”
Section: Introductionmentioning
confidence: 99%